Overlapping Time in the Assassination Story For Haider Haider (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The modern and contemporary Arab critical lesson has worked on the study of time, as a structural artistic technique upon which the story construction is established, which makes the creator in a state of constant search for a temporal form for his vision and position of the world . Here ,the research requires careful attention to the following question :Based on the relationship between the external historical chronological natural time and the private narrative time, how does the storyteller reshape the refractions of the shadows left by the outer time in his consciousness in order to reshape his own time that expresses his philosophy and vision of the reality of living.Time is manifested in its three dimensions , the past , the present and future , in a sequence that flows through the modesty of the narrative character, which is determined through the process of time and changes with its continuity, and the present comes as a result of the past , carrying the future in its folds.